Prevalence of BoHV-1 seropositive and BVD virus positive bulls on Irish dairy farms and associations between bull purchase and herd status. Issue 1 (December 2015) - Martinez-Ibeas, A.; Power, Clare; McClure, Jennifer; Sayers, Riona
Abstract Background BVD and IBR are contagious viral diseases highly prevalent in Irish cattle. Despite their significant reproductive and economic impact very little is known about the BVD and IBR status of stock bulls (a bull used for breeding purposes). There are still a high proportion of dairy farms in Ireland that rely on the use of a bull for breeding cattle and ensuring the fertility of the bulls is of paramount importance for the efficiency of the farms. The prevalence of BoHV-1 and BVD in stock bulls in Irish dairy herds has never been investigated. The objectives of this study therefore were: (i) to provide descriptive, observational data on the use of stock bulls on Irish dairy farms; (ii) to investigate the BVD and BoHV1 status of a sub-set of stock bulls; (iii) to investigate factors associated with BVD and BoHV1 status of stock bulls and (iv) to investigate factors associated with dairy herd status for BVD and BoHV1, including any associations with the use of stock bull. A total of 529 blood samples from bulls involved in the dairy breeding process were analysed for BVD virus using RT-PCR, and BoHV-1 antibodies by ELISA test. A total of 305 different dairy herds took part in the study and the overall BVD and BoHV-1 herd status was determined by ELISA using four bulk tank milk samples over the 2009 lactation. Logistic regression was used to investigate the associations between the stock bulls and BVD and BoHV-1 herd and individual status. Results Of the 305 total participating farms, 235 farms (77 %) had at least one bull and 167 farms had purchased bulls. Two bulls (0.4 %) out of 529 tested were found positive for BVD virus and 87 (16.7 %) tested seropositive for BoHV-1. Some significant associations were identified between the purchase of bulls and both viral diseases. Purchased bulls were three times more likely to be seropositive for BoHV-1 than homebred bulls. In the same way, herds with purchased bulls were three times more likely to be classified as seropositive for BVD and four times more likely to have evidence of recent BoHV-1 circulation than farms where all the bulls were homebred. Conclusions The prevalence of BoHV-1 and BVD in stock bulls in Irish dairy herds has never been investigated. This study highlights the widespread use of stock bulls in Irish dairy herds, as well as the high rate of exchange of bulls between farms. Significant associations were found between the origin of the bull and their serological BoHV-1 status. In keeping with these results, bulls with higher number movements between farms were more likely to be seropositive for BoHV-1.